VIRTUAL MODEL OF A CONTACTLESS AC GENERATOR - ZENOVYCH, OLEKSANDR; VASYLENKO, ROMAN; HEORHIIEV, YURIY; EIDELSHTEIN, GENNADY; PAYANOK, OLEKSANDR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Currently, the main sources of alternating current electrical energy on airplanes and helicopters are contactless synchronous generators of the ГТ type with an alternating current exciter and rotating rectifiers.When conducting research on power generation systems, for example, in order to implement a diagnostic method based on monitoring electrical parameters with subsequent special analysis of the received signal, it is necessary to have reference parameters (voltages, currents, transient characteristics, voltage and current spectra) of the machine. These parameters can be obtained experimentally or by modeling, because the machine parameters in the event of typical failures cannot always be obtained experimentally. This circumstance is associated with the complexity or impossibility of physically simulating failures. For this purpose, various types of application software packages are used (for example, Matlab/Simulink, LabVIEW/Control Design and Simulation), which allow modeling complex dynamic systems, including those described by nonlinear differential equations.For example, synchronous generator models from the SimPowerSystems section of the Matlab/Simulink environment allow for good results in modeling normal generator operation. At the same time, standard models have limited failure simulation capabilities, allowing only open circuits and short circuits of windings to be simulated. To simulate other electrical and mechanical faults, standard models are usually upgraded or special ones are developed to simulate typical failures, in particular: stator winding or insulation failure, rotor winding or insulation failure, bearing failure, rotor mechanical integrity failure, stator mechanical integrity failure. As a review of publications has shown, no attention is paid to failures of the electronic part of cascade generators.The proposed work presents a virtual model of a synchronous generator, built in the MatLab/Simulink simulation environment. The model is built taking into account the design features of cascade synchronous generators of the ГТ series: the presence of three generators in the machine - a magnetoelectric exciter, an electromagnetic exciter, an electromagnetic main generator; an uncontrolled three-phase rotating rectifier; a phase-pulse voltage regulator with a controlled rectifier. The proposed model allows you to study the operation of the generator in normal operation and in the event of typical generator failures, including electronic elements.This model can be useful in studying the processes occurring in AC generation systems with ГТ series generators both in normal operation and in the event of failures. Therefore, the development of this virtual model in the Matlab/Simulink environment of a contactless synchronous generator allows you to obtain both reference parameters and parameters in the event of failures
Keywords: synchronous generator; virtual model; MatLab/Simulink simulation environment; voltage regulator; three-phase rectifier